2013
DOI: 10.1177/0363546512473818
|View full text |Cite
|
Sign up to set email alerts
|

Match Injuries in English Youth Academy and Schools Rugby Union

Abstract: Overall, the incidence of injury for youth rugby was lower than for previous studies in senior rugby, but injury patterns (location, type) and causes were similar. The study confirmed that match injury incidence was significantly greater in elite academy youth rugby union than schools rugby. The results suggest that the specific focus for injury risk management in youth rugby should be on players' tackle technique and prevention strategies for knee and shoulder injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
140
8
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(174 citation statements)
references
References 38 publications
24
140
8
2
Order By: Relevance
“…Literature reports the tackle to be the most dangerous phase of play as 40 -64% of injuries were sustained as a result of a tackle. [5,7,8,12] This also holds true for koshuis rugby based on the data presented here.…”
Section: Tackle-related Injury Ratesupporting
confidence: 78%
See 4 more Smart Citations
“…Literature reports the tackle to be the most dangerous phase of play as 40 -64% of injuries were sustained as a result of a tackle. [5,7,8,12] This also holds true for koshuis rugby based on the data presented here.…”
Section: Tackle-related Injury Ratesupporting
confidence: 78%
“…injuries exposure time 1.96 ± players in 2008 (15.2 injuries/1 000 playing hours). [7] This trend is supported by Jakoet and Noakes, [6] McIntosh et al [11] and PalmerGreen et al, [8] who found an increase in injury rate with increased age and level of play.…”
Section: Tackle-related Injury Ratementioning
confidence: 65%
See 3 more Smart Citations